FAKTOR YANG BERPENGARUH TERHADAP KINERJA PEGAWAI BIDANG PENGAIRAN DAN ENERGI SUMBER DAYA MINERAL DINAS PEKERJAAN UMUM KARANGANYAR - -, Sugimin -; -, Suharno - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2011)
AbstraCT The purpose of this study is to analyze the significance of the influence of leadership, supervision, and job satisfaction on employee performance in the field of Water and Energy and Mineral Resources Department of Public Works Karanganyar. The population is the staff of the Water Sector and Energy and Mineral Resources Department of Public Works Karanganyar by 55 people. The results show there is a significant effect of leadership on employee performance, (2) there is no significant effect of surveillance, to employee performance, (3) there is no significant effect of job satisfaction on employee performance. (4) the independent variable (leadership, supervision and job satisfaction) variables contributing influence on employee performance by 12,4 percent. Keywords: Leadership, Supervision, Job Satisfaction, Performance